Sistema de gestão ambiental no verdegreen hotel João Pessoa/PB: um estudo de caso sob a perspectiva da resource-based view - Colombo, Ciliana Regina (2015)
The pressure for a new pattern of sustainable development has required of modern organizations the search for competitiveness, but respecting and considering environmental issues. In this sense, a tool that acts in the implementation of structured strategies is the environmental management system (EMS), such assessments are not performed on specific objects, like the EMS. Thus, the aim of this study was to evaluate the resources and capabilities (environmental strategies) of the EMS adopted by the Verdegreen Hotel, identifying which of these have the potential to generate competitive advantage. For this, this exploratory-descriptive casestudy used as data collection tools: a bibliographic survey, semi-structured interviews, documental research and direct observation. The interpretation of the results and the consolidation of information were conducted from a qualitative approach, using two techniques of data analysis, namely: content analysis and analysis through VRIO model. The results show that the hotel is quite structured in relation to their EMS, and it has benefits related to improvement of the management of environmental factors, to the strengthening of its image and to the gains in competitiveness. On the other hand, the main difficulties for the implementation of the system are related to employees and suppliers. With regard to environmental strategies adopted, of the 25 strategies identified, 10 showed the potential to generate competitive advantage